Implementasi Program Intervensi CBT pada Anak dengan Masalah Perilaku - Keyza Salma Salsabila; Leory Yunistia Jasmine; Yoga Budhi Santoso (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Children with emotional and behavioral difficulties are children who have trouble adjusting to their social environment. This can affect their academic and functional abilities in daily life. Children with emotional dysregulation and aggressive behavior are particularly vulnerable to experiencing a series of social problems due to their emotional and behavioral difficulties. Therefore, emotional and behavioral intervention is needed to help them develop new adaptive behaviors and reduce maladaptive behaviors. One intervention method that is often used to reduce children's abberant behavior is CBT, especially the CBT-AAC model, which focuses on three dimensions, namely anger management skills, problem-solving skills, and social skills. This study used the SSR (Single Subject Research) research model on a 15-year-old boy with behavioral problems (Conduct Disorder) with symptoms of aggressive dominance. The CBT program was implemented with a total of 5 meetings using various approaches that focused on the child's aggressive problems. The behavior frequency graph then showed a significant decrease in aggressive behavior and positive changes in the cognitive process.